Identification of bioactive compounds in mountain soursop (Annona montana Macf.) and their potential as a source of antioxidants - Apria, Desra; Warsiki, Endang; Sailah, Illah (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2026)
Annona montana Macf. (mountain soursop), a member of the Annonaceae family, is a tropical fruit with promising yet underexplored bioactive potential. This study aimed to comprehensively evaluate the phytochemical profile and antioxidant activity of mountain soursop fruit extract. Bioactive compounds were identified using Gas Chromatography–Mass Spectrometry (GC-MS), while antioxidant capacity was assessed through the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay under controlled conditions. GC-MS analysis revealed the presence of 80 compounds, including flavonoids, alkaloids, terpenoids, and fatty acids, many of which are well documented for their pharmacological and functional properties. The extract demonstrated very strong antioxidant activity with an IC50 value of 18.85 ppm, markedly surpassing several widely recognized natural antioxidants. These results highlight mountain soursop fruit as a valuable natural reservoir of bioactive metabolites with diverse biological functions. The findings further support its potential utilization in the development of functional foods, health-promoting formulations, nutraceuticals, and cosmetics, particularly those designed to mitigate oxidative stress and protect long-term skin health.